2007
DOI: 10.1016/j.dr.2006.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Classes in the balance: Latent class analysis and the balance scale task

Abstract: Latent class analysis (LCA) has been successfully applied to tasks measuring higher cognitive functioning, suggesting the existence of distinct strategies used in such tasks. With LCA it became possible to classify post hoc. This important step forward in modeling and analyzing cognitive strategies is relevant to the overlapping waves model for strategy development [Siegler, R. S. (1996). Emerging minds: The process of change in children's thinking. New York: Oxford University Press.]. However, so far, develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Exploratory analyses with age and gender were conducted. Gender did not relate to the pretest, posttest, or difference score (posttest minus pretest), which was in line with gender being not significant as a covariate in an LCA on the balance beam test (Boom and Ter Laak, 2007). The present results showed that gender also did not relate to a difference score.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Exploratory analyses with age and gender were conducted. Gender did not relate to the pretest, posttest, or difference score (posttest minus pretest), which was in line with gender being not significant as a covariate in an LCA on the balance beam test (Boom and Ter Laak, 2007). The present results showed that gender also did not relate to a difference score.…”
Section: Discussionsupporting
confidence: 78%
“…In addition to Strategies 1, 2, 4, and the Addition Strategy, two classes (out of six) did not match any strategy. A later study with 5-to 14year-old participants and two covariates of class membership (age and working memory) revealed comparable classes, but the class representing Strategy 4 was not found (Boom and Ter Laak, 2007). Boom and Ter Laak (2007) attributed the absence of Strategy 4 to the inclusion of only few older participants.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…We indeed found a fade out effect for the intervention. Second, from a statistical point of view, this study is innovative in the sense that the used latent growth curve model incorporated categorical responses to the tasks, which allowed us to model gradual changes in levels of reasoning (Boom & Ter Laak, 2007). Third, our cohort-sequential research design enabled us to "re-use" student groups per instruction condition, whereby the groups served as their own control group, depending on the specific cohort.…”
Section: Limitations Strengths and Future Researchmentioning
confidence: 99%